Socratic Questioning Method in The Colloid System Topics Using The Participatory Action Research (PAR) - Khusnul Lusi Nursyam Syanas; Sulistyo Saputro; Nurma Yunita Indriyanti; Sri Mulyani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
The purpose of this research is to identify how lesson plans prepared based on socratic questions can improve critical thinking skills. Research method used is Participatory Action Research (PAR), data collection techniques through interviews and questionnaires. It is expected that the results of the research can be applied in schools specifically to produce lesson plans in colloidal learning integrated with TPACK (Technological Pedagogical Content Knowledge). The results showed the teacher gave a positive assessment of 85% on the socratic questions contained in the lesson plan. This will provide stimulants to students in order to able to argue and practice their critical thinking skills. Postgraduate student participants also gave a positive response of 87.5%. It can be concluded that both teacher participants and postgraduate students agree with the application of socrates questions to students because they have a positive impact on critical thinking skills. Thus, this initial stage of research can proceed to the next stage of PAR research.